Morocco’s Job Market Policy Over the Last Fifteen Years: Graduate Recruitment in the Public Sector - JAOUAD RADOUANI (African Journal of Governance and Development, 2015)
This paper’s aim is to discuss Morocco’s last fifteen years’ job market policy and youth recruitment in the public sector. It is a know fact that there are youths who struggled before being recruited in the public sector, this paper will attend to the effects of three successive governments’ policies on the Moroccan labour market. Knowing that the rates of unemployment, especially among graduates, is doubling the overall unemployment rate that is currently at ten percent (10), Morocco, in spite of the number of schemes it has investigated to assist graduates to find work, still faces a growing wave of demonstrations regularly organised by frustrated protesters calling for their right for a job opportunity. The three last ruling Moroccangovernments, namely the ones led by The Socialist Union of Popular Forces Party, The Independence Party, and The Justice and Development Party, contributed through different political plans to solve the problem of unemployment among graduates, or at least to reduce their numbers and temporarily absorb their anger; however, in despite those efforts, nothing is forthcoming on the ground. The objective here is to highlight the policies of previous governments and show pitfalls of the current one, whose policy are proving to be a total failure in comparison to previous ones.